SAR Retracking in the Arctic: Development of a year-round retrackers system. Issue 6 (15th September 2018) - Schulz, Ann-Theres; Naeije, Marc
Abstract: Given its polar orbit, CryoSat-2 provides frequent, high-resolution SAR altimeter measurements of the Arctic region over changing terrain ( e.g. ice, water and sea ice). The purpose of this research is to improve SAR waveform retracking in the Arctic region by analysing different retrackers on their performance in varying (Arctic) conditions and combine the positive behaviours into one optimal retrackers system. Based on the accuracy and precision performance, four retrackers are evaluated in order to determine this retrackers system: the empirical primary peak centre of gravity, the primary peak threshold and the ESA retracker, as well as the physical SAMOSA3 retracker. Empirical retrackers determine the retracking point depending on the retrieved waveform statistics, while physical retrackers take the system characteristics, the geometry and the surface properties into account. Three sea surface types are considered in this research: ocean, sea ice, and ice leads. For the majority of the months, SAMOSA3 has the highest accuracy for ocean waveforms as its physical full-analytic approach provides a good fit for the predictable ocean waveforms. The primary peak retrackers have the best precision performance for irregular waveforms like sea ice and ice leads. The year-round retrackers system includes per month the most accurate retracker for ocean waveforms and the best precision retracker for sea ice and leads. To remove the bias caused by combining different retracking algorithms, four bias removal strategies are developed and evaluated on their accuracy and precision performance. The retrackers system with the primary peak centre of gravity as a basis retracker and a mean bias removal approach performed best, as it has a precision improvement of 47.1% with respect to retracking all waveform classes with the primary peak COG retracker solely. By applying the developed optimal retrackers system and using the bias removal strategy, the mean standard deviation of the altimeter measurements in the Kara Sea study area is reduced from 6.7 cm to 3.6 cm.